Assessment of FMO3 SNPs in Relation to TMAO in Generally Healthy United States Adults. (7th June 2021) - James, Kristen; Gertz, Erik; Kirschke, Catherine; Huang, Liping; Stephensen, Charles; Bennett, Brian
Abstract: Objectives: The hepatic enzyme flavin monooxygenase 3 (FMO3 ) oxidizes many metabolites including trimethylamine to the atherogenic molecule trimethylamine n-oxide (TMAO). Variants in the open reading frame of the FMO3  gene alter the enzyme's activity; therefore, we genotyped two a priori missense FMO3 SNPs in a cohort of unmedicated healthy adults. We hypothesized that the SNPs might affect the activity of the encoded enzyme leading to reductions in circulating TMAO. FMO3 expression is upregulated by estrogen, thus we also assessed the relationship of the SNPs and TMAO in pre- and postmenopausal women. Methods: DNA was extracted from whole blood from 349 subjects (182 women) who were enrolled in a cross-sectional study at the USDA/ARS WHNRC. SNPs rs2266782 (G > A, p.Glu158Lys) and rs2266780 (A > G, p.Glu308Gly) were genotyped using TaqMan SNP genotyping kits and PCR. TMAO was purified from fasted plasma and quantified using high resolution LC-MS. Regression models were built to assess the relationship of the SNPs to TMAO in the full cohort and by self-reported menopausal status in women. Models assessing the full cohort were adjusted for plasma cystatin C and a sex*age interaction, whereas the menopausal analysis was adjusted for cystatin C. Results: The cohort's minor allele frequencies were 36.5% and 17.5% for SNPs rs2266782 and rs2266780, respectively, which were consistent with the genome aggregation exome reports. For both SNPs, median TMAO concentrations increased in individuals carrying the risk alleles, however the differences by genotypes were not significant. In women, the AA genotype at rs2266780 was associated with reduced TMAO levels in pre-, but not postmenopausal women (P = 0.01). This effect was not identified in females with AG or GG genotypes, regardless of their menopausal state. Conclusions: Effects of the evaluated FMO3 SNPs on TMAO levels were not identified in the full cohort. However, the SNP rs2266780 was associated with reduced TMAO in premenopausal women with the AA genotype but not women with the AG or GG genotypes, nor those who were postmenopausal. This finding reinforces previous observations that risks for cardiovascular diseases increase after menopause in women. Funding Sources: The Beef Checkoff, R01HL128572; USDA-ARS 2032–53, 000–001–00-D, 2032–51, 530–022–00-D, and 2032–51, 000-004–00D; NCATS NIH UL1 TR001860.